Interactional Communication in Developing Digital Marketing during Pandemic Era - Damayanti Wardyaningrum; Ramadhanty Pratiwi; Elin Fitriyanti; Priska Febi Hikmawati; Rafi Herjuno (Universitas Muhammadiyah Yogyakarta, 2023)
The digital era has brought a massive impact on business development in Indonesia., However, the Covid-19 pandemic has crushed almost all small and medium enterprises (SMEs), and they are currently trying to stand and rise again in the post-pandemic. This study aims to identify the business development process in SMEs by using digital methods carried out by youth groups in pandemic situations from interactional communication perspectives. The concept used in this study is an interactional communication model with the element of individual meaning toward the social environment and individual field of experience. This research method is descriptive qualitative through focused group discussion (FGD). The result found that from the interactional communication process, the meaning interpreted by the group member toward their social environment was the identification of a number of problems faced by the SME owner. Other than that, there was also the meaning-making about building enterprises by utilizing digital media for marketing, especially in creating a platform for content management. Groupmembers’ different field of experience has brought opportunities to respond to eachother’s problem. There are also opportunities to create a new network and collaboration in searching for a solution to build a business with a digital marketing method.